Variation in the distribution and properties of Circumpolar Deep Water in the eastern Amundsen Sea, on seasonal timescales, using seal-borne tags - Mallett, Helen K. W.; Boehme, Lars; Fedak, Mike; Heywood, Karen J.; Stevens, David P.; Roquet, Fabien (Geophysical Research Letters, 2018)
In the Amundsen Sea, warm saline Circumpolar Deep Water (CDW) crosses the continental shelf toward the vulnerable West Antarctic ice shelves, contributing to their basal melting. Due to lack of observations, little is known about the spatial and temporal variability of CDW, particularly seasonally. A new dataset of 6704 seal‐tag temperature and salinity profiles in the easternmost trough between February and December 2014 reveals a CDW layer on average 49 db thicker in late winter (August to October) than in late summer (February to April), the reverse seasonality of that seen at moorings in the western trough. This layer contains more heat in winter, but on the 27.76 kg/m 3 density surface CDW is 0.32° C warmer in summer than winter, across the northeastern Amundsen sea, which may indicate wintertime shoaling offshelf changes CDW properties onshelf. In Pine Island Bay these seasonal changes on density surfaces are reduced, likely by gyre circulation.